Severe Dengue Infection in a Pediatric Case of Kidney Failure: Lesson Learned From a Management Perspective: Severe dengue in a child of kidney failure - Tonny, Rummana; Al Mamun, Abdullah; Chowdhury, Aditi; Begum, Afroza (Journal of Pediatric Nephrology, 2025)
Background and Aim: Dengue viral infection has become a major public health concern worldwide. This situation worsens when accompanied by other comorbidities. There is a lack of published literature on dengue viral infection in pediatric patients with kidney failure undergoing maintenance hemodialysis. Case Presentation: We report the case of a child with kidney failure who underwent maintenance hemodialysis and presented with dengue shock syndrome. Conclusion: Prompt diagnosis, close monitoring, and individualized treatment regimens are crucial for patient survival. A significant dilemma exists in managing such cases that may guide physicians in the future.